2015
DOI: 10.4025/enfoque.v34i2.26818
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho acadêmico em métodos quantitativos nos cursos de Ciências Contábeis

Abstract: Enf.: Ref. Cont. UEM-Paraná v. 34 n. 2 p. 37-50 maio/ago de 2015 RESUMO Este estudo investigou variáveis que explicam o desempenho acadêmico (academic achievement) nas disciplinas de métodos quantitativos no curso de ciências contábeis. Realizou-se uma pesquisa empírica na Universidade Federal do Pará com objetivo de encontrar proxies associadas à variável dependente desempenho acadêmico. Assim, com a finalidade de ratificar os achados desta pesquisa, foi realizado teste estatístico de análise de regressão por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
0
3
0
5
Order By: Relevance
“…Andreoli and De Martino (2012) gathered evidence that the patterns of college students in the morning shift were relevantly different from the ones of the night shift and that those performance (morning-shifted) was higher than these (night-shifted). The findings of the research by Farias, Alves and Farias (2015) also support that day shift students (morning and afternoon) have significantly better performances than those of the night shift. In the research of Mallmann et al (2021) it was found that full-time students performed better than those in the morning, afternoon, and night shifts.…”
Section: Institutional Variablesmentioning
confidence: 56%
See 1 more Smart Citation
“…Andreoli and De Martino (2012) gathered evidence that the patterns of college students in the morning shift were relevantly different from the ones of the night shift and that those performance (morning-shifted) was higher than these (night-shifted). The findings of the research by Farias, Alves and Farias (2015) also support that day shift students (morning and afternoon) have significantly better performances than those of the night shift. In the research of Mallmann et al (2021) it was found that full-time students performed better than those in the morning, afternoon, and night shifts.…”
Section: Institutional Variablesmentioning
confidence: 56%
“…The finding is consistent with the research of Mallmann et al (2021), who also found that the full shift had the best academic performance. In the case of Farias et al (2015), the full-time shift was not an option. But it was found that the students of the day shift (morning and afternoon) performed better than the students of the night.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…O interesse em torno da tipografia no design gráfico se traduz pela preocupação quanto à "verbalização visual" do simbolismo do seu conteúdo. Farias (1998) define tipografia como as práticas de criação e utilização de caracteres ortográficos (letras) e para-ortográficos (números e pontuações) para reprodução.…”
Section: Tipografia Para Ambientes Digitaisunclassified
“…As fontes carregam consigo uma expressão formalizada da tipografia. Na opinião de Farias (1998), pela observação da história, a tipografia sempre foi condicionada pelo propósito de agir como uma interface visual da linguagem verbal, excluindo o tempo pós-moderno que foge ostensivamente a este padrão. Pode-se dizer que a tipografia no pós-moderno, conforme Gruszynski (2008), está além da escrita.…”
Section: Tipografia Para Ambientes Digitaisunclassified
“…Adicionalmente, na Tabela 3, foi analisado o desempenho acadêmico por forma de ingresso, foi comparado o desempenho acadêmico de ingressantes por Vestibular e por SiSU. Quando analisamos o desempenho do CRA por grau de ensino (Bacharelado e Licenciatura) e por turno (Integral e Noturno) vemos pelo resultado na Tabela 4 que o grauMAIOR et al, 2011;FARIAS, 2015;DÁRIO, 2017). Tal resultado pode ser explicado pelo perfil do estudante do turno noturno que provavelmente trabalha durante o dia e se dedica aos estudos apenas à noite.…”
unclassified